2016
DOI: 10.1177/0954008315600228
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanosilica and methyl methacrylate–butadiene–styrene core–shell rubber particles on the physical-mechanical properties and cure kinetics of diglycidyl ether of bisphenol-A-based epoxy resin

Abstract: The influence of nanosilica and methyl methacrylate–butadiene–styrene (MBS) core–shell rubber particles on the physical-mechanical properties and cure kinetics of diglycidyl ether of bisphenol-A-based epoxy resin (EP)/dicyandiamide were investigated using tensile test, dynamic mechanical thermal analysis, and differential scanning calorimetry under dynamic conditions. The results indicated that inclusion of core–shell rubber particles and nanosilica (NS) into EP increased cure onset, peak and end temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 47 publications
0
16
0
2
Order By: Relevance
“…It has a good balance of transparency and impact resistance (Takahashi et al, 2015). Styrene and methyl methacrylate (MMA) are grafted onto styrene butadiene rubber (SBR) or poly(butadiene) (PB) particles so that MBS is a typical core-shell rubber modifier (Mousavi & Amraei, 2015;Ren et al, 2014). MBS is an impact modifier polymer that contains 0.01 to 5 percent (w/w) of the polymers of at least one compound of the formula, wherein R 1 and R 2 are C 1 to C 4 alkyl, R 3 and R 4 are HC 1 to C 4 alkyl, or 4-hydoxy 2'-R 2 5'-R 1 -phenyl.…”
Section: Introductionmentioning
confidence: 99%
“…It has a good balance of transparency and impact resistance (Takahashi et al, 2015). Styrene and methyl methacrylate (MMA) are grafted onto styrene butadiene rubber (SBR) or poly(butadiene) (PB) particles so that MBS is a typical core-shell rubber modifier (Mousavi & Amraei, 2015;Ren et al, 2014). MBS is an impact modifier polymer that contains 0.01 to 5 percent (w/w) of the polymers of at least one compound of the formula, wherein R 1 and R 2 are C 1 to C 4 alkyl, R 3 and R 4 are HC 1 to C 4 alkyl, or 4-hydoxy 2'-R 2 5'-R 1 -phenyl.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, the samples were gently poured into mold and cured at 120°C for 90 min. The details of experimental setup were according to Mousavi and Amraei previous work ( Figure 2) [23]. Details of the composition of the formulations are listed in Table 2.…”
Section: Sample Preparationmentioning
confidence: 99%
“…These tougheners decrease modulus, tensile strength, and glass transition temperature (T g ); so in order to enhance the mechanical and thermal properties, the toughened EPs are reinforced by nanosilica (NS) particles. Mousavi and Amraei [23] used EP-CSR-NS composites and found that NS partially offsets the reduction in properties caused by CSR.…”
Section: Introductionmentioning
confidence: 99%
“…MBS mengandung polimer karet pada susunan elastomernya yaitu styrene-butadiene rubber (SBR) sehingga dapat meningkatkan sifat mekanik polimer (Ren et al, 2014;Liu et al, 2014;Zhou et al, 2012). MBS juga banyak digunakan sebagai kompatibiliser baik untuk plastik (Moolsin & Saksayamkul, 2016;Mousavi & Amraei, 2015;Liu et al, 2014). Montmorillonite (MMT) adalah salah satu mineral tanah liat alami yang memiliki luas permukaan yang besar.…”
Section: Pendahuluanunclassified
“…Dari persamaan (1) Tabel 4 menunjukkan karakteristik dinamik dari kompon NBR/EPDM. Data karakteristik ini didapat dari pengujian dengan menggunakan rheometer, yang menunjukkan mH (torsi maksimum) dan mL (torsi minimum).…”
Section: Reologi Campuran Nbr/epdmunclassified